Functional Genomics of the 9p21.3 Locus for Atherosclerosis: Clarity or Confusion? - Chen, Hsiao-Huei; Almontashiri, Naif A. M.; Antoine, Darlène; Stewart, Alexandre F. R. (Current cardiology reports, 2014)
The 9p21.3 locus was the first to yield to genome-wide association studies (GWAS) seeking common genetic variants predisposing to increased risk of coronary artery atherosclerotic disease (CAD). The 59 single nucleotide polymorphisms that show highest association with CAD are clustered in a region 100,000 to 150,000 base pairs 5′ to the cyclin-dependent kinase inhibitors CDKN2B (coding for p15 ink4b ) and CDKN2A (coding for p16 ink4a and p14 ARF ). This region also covers the 3′ end of a long noncoding RNA transcribed antisense to CDKN2B ( CDKN2BAS , aka ANRIL for antisense noncoding RNA at the ink4 locus) whose expression has been linked to chromatin remodeling at the locus. Despite intensive investigation over the past 7 years, the functional significance of the 9p21.3 locus remains elusive. Other variants at this locus have been associated with glaucoma, glioma, and type 2 diabetes mellitus, diseases that implicate tissue-resident macrophages. Here, we review the evidence that genetic variants at 9p21.3 disrupt tissue-specific enhancers and propose new insights to guide future studies.